Rekam Medis Elektronik Berbasis Cloud Computing: Pertanggungjawaban Hukum Akibat Kebocoran Data Pasien - Yanto, Oliviani; Putri, Kezia Annabel Rinda; Prananingrum, Dyah Hapsari (Universitas Widya Gama Malang, 2025)
The primary objective of this research is to analyze legal liability in breach of patient’s medical record in SatuSehat platform that provides Cloud Computing-based electronic medical record. This research is a document study or normative legal research that uses conceptual approach and statute approach. The Omnibus Health Law and Minister of Health Regulation about Medical Records require in implementation of medical records must be in electronic form or electronic medical records. As a result of this obligation, legal issue arises related to the protection and confidentiality of patient data which stored and managed by electronic medical record’s administrator. Focus of this research is the implementation of a cloud computing-based electronic system through a system developed by the Ministry of Health which is SatuSehat. This research shows that the party who legally liable for the implementation of Cloud Computing-based electronic medical records is the Ministry of Health, the reason is because there is a transfer of legal liability from healthcare facility to the Ministry of Health because initially the patient data is received by the healthcare facility, and then integrated into the Cloud Computing-based electronic medical record. So because of that, Ministry of Health as a party who has full authority of the data that has been received and integrated in SatuSehat system must held the responsibility if there is a problem with the data. Therefore, the purpose of this study is not only to analyze of the legal responsibility but also to provide legal basis for the protection of hospitals, doctors and patients in the event of a data leak in the SatuSehat Platform. In addition, authors analyzes the protection principles applied in Indonesia with three pillars of patient health data protection applied in the United States.